FAKTOR-FAKTOR YANG MEMPENGARUHI IBU MEMBERIKAN MAKANAN TAMBAHAN PADA BAYI USIA KURANG DARI 6 BULAN DIPUSKESMAS SIDOMULYO TAHUN 2019 - Sari, Endah Purwani (Menara Ilmu, 2019)
Complementary food or drink Asi is a valuable food given to infants aged 6 months to 24 months to meet their nutritional needs. Given solids in addition to energy and nutrient infants aged 6 months or older. The purpose of this study was to determine the factors that affect the mother giving extra food to infants younger than 6 months in Puskesmas Sidomulyo. This type of research is quantitative descriptive design conducted in April in the Puskesmas Sidomulyo. file collection using the questionnaire. Subjects were all mothers with infants younger than 6 months that aims to identify the factors that cause mothers to give extra food to infants younger than 6 months in Sidomulyo. The file was analyzed by univariate analysis. Based on the research that has been conducted on factors affecting the mother giving extra food to infants younger than 6 months in the working area health centers Sidomulyo 2019, found that the factors that affect the mother giving extra food to infants younger than 6 months, namely Lack of Myth 57 cases (79.2%), and customs 55 cases (77%) The conclusion is based on research that has been conducted shows that of the factors causing mothers to give extra food to infants from 6 months of age kurng namely Less information, Myths, and socio-cultural changes. But more dominant than Myth factor that as many as 57 cases (79.2%). Keywords: PMT (Feeding) Reference: 15 Reference (2007-2016)